Pengaruh Kualitas Produk Terhadap Kepuasan Konsumen Pada UD. Sumber Rezeki Kecamatan Panyabungan Kabupaten Mandailing Natal - Rika Yanti Pulungan; Vebri Sugiharto; Ade Khadijhatul Z Hrp (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
The Influence of Product Quality on Consumer Satisfaction at UD. Source of Fortune, Panyabungan District, Mandailing Natal Regency. This research aims to analyze the influence of product quality on consumer satisfaction at UD. Source of Fortune. The method used is quantitative research with a sample of 99 respondents, taken using the Slovin formula. Data was collected through questionnaires and analyzed using simple linear regression. The research results show that product quality has a positive and significant influence on consumer satisfaction, with a t-count value of 21.726, much higher than the t-table of 1.661. The R Square value of 0.830 shows that 83% of consumer satisfaction is influenced by product quality. This research concludes that improving product quality can increase consumer satisfaction, so it is important for UD. Sumber Rezeki continues to improve the quality of its products in order to maintain and increase customer loyalty.